Does cost sharing do more harm or more good? - a systematic literature review - Katarzyna Kolasa; Marta Kowalczyk (BMC, 2016)
Abstract Background There are positive and negative consequences of the implementation of out of pocket (OOP) payments as a source of the healthcare financing. On the one hand, OOP burden increases awareness of treatment costs and limits unnecessary use of healthcare services. On the other hand, it may prevent the sick from accessing needed care. Consequently there are several aspects that ought to be taken into consideration while defining the optimal structure of OOP payments. The objective of this study was twofold. Firstly, it was to understand what actions are taken to decrease the OOP burden. Secondly, it was to address the question whether the implementation of any form of formal OOP payments may impact negatively upon fairness in financial contribution. Methods The literature search was conducted using the Pubmed, Embase, Cochrane Library and Center of Review and Dissemination databases. Only studies which measured the Kakwani index of progressivity in at least two time points were included. Articles written in English published between January 2004 and September 2015 were searched. No geographical restriction was imposed. An increment of more than 0.10 in the Kakwani index was considered as a significant health policy impact. Results In total 16 publications were included, of which nine studied attempts to decrease the OOP burden, four described the consequences of the introduction of formal fees, and three covered both topics. Overall, a significant health policy impact was noted in four cases. All of them related to a reduction in the OOP burden, with three and one noting a change towards the progressivity and regressivity of direct healthcare payments respectively. Among jurisdictions which introduced formal fees, none study noted a significant impact on the regressivity of OOP spendings. Conclusions In the majority of cases, a health policy impact on the distribution of OOP health payments was insignificant. The reduction of OOP burden cannot be achieved successfully without adequate extension of healthcare coverage or engagement of other sources of healthcare financing. When formal fees are being introduced, protection against catastrophic healthcare payments is needed for the most vulnerable groups.